Adaptive Skills and Academic Achievement in Latino Students. Issue 4 (2nd October 2017) - Raines, Tara C.; Gordon, Melissa; Harrell-Williams, Leigh; Diliberto, Rachele A.; Parke, Elyse M.
ABSTRACT: Interventions developed to improve adaptive skills can improve academic achievement. The authors expanded this line of research by examining the relationship between performance on a state proficiency exam and adaptive skills classifications on the Behavioral Assessment System for Children, Second Edition parent and teacher reports. Participants included 392 Latino students, Grades 2–6 in a large urban school district. Ordinal regression models were used to assess relationships between student academic proficiency level and adaptive skills classifications. Students classified as having higher adaptive skills by teachers were more likely to be classified as proficient or higher in reading and mathematics. These findings further support the relationship between adaptive skills and academic achievement. Implications for future research and practice are discussed.